STUDI KORELASI: PERSEPSI RISIKO MENCARI BANTUAN MEDIS DAN LITERASI KESEHATAN MENTAL PADA MAHASISWA KESEHATAN - Nurdin, Andi Ardiansyah; Ramdani, Aulia; Qamila, Asyaratun (Media Penelitian dan Pengembangan Kesehatan, 2025)
Mental health has become one of the non-communicable diseases with a globally increasing prevalence. The negative stigma surrounding mental health remains strong in society, making early intervention crucial in preventing more severe mental disorders. The risk perception in seeking medical help for mental health issues needs to be accompanied by adequate mental health literacy. The research variables consist of risk perception to seek medical help and mental health literacy. This study aimed to examine the correlation between risk perception to seek medical help and mental health literacy using a quantitative approach with a cross-sectional design. A total of 399 respondents participated in the study, selected using an accidental sampling technique. Data collection was conducted using two scales: the Mental Health Literacy in Young Adults scale and the Risk Perception Scale of Medical Help-Seeking Behaviour. The findings indicate that mental health literacy is predominantly in the high category, while the perceived risk of seeking medical help is mostly in the low category. The chi-square statistical test showed a significance value of 0.009 < 0.05, indicating a significant relationship between mental health literacy and the perceived risk of seeking medical help among health students. The practical outcome of this study is anticipated to support universities in formulating policies centered on preventive and promotive mental health strategies, aiming to improve mental health literacy and reduce perceived risks associated with mental health issues.